GAMBARAN TINGKAT PENGETAHUAN TENTANG MENYIKAT GIGI SEBELUM DAN SESUDAH PENYULUHAN DENGAN MEDIA SENI MONTASE PADA SISWA/I KELAS III SDN 067247 KEC. MEDAN TUNTUNGAN - Nurhamidah; Atika Fatin Nabil; Akhmad Rifa (Poltekkes Kemenkes Medan, 2023)
Dental and oral health is an inseparable part of overall body health. Currently, dental health problems are still a second priority, especially for Indonesian people, even though a seemingly trivial toothache can trigger a number of dangerous diseases, and dental disease has even been reported to cause death. To increase knowledge, this can be done through counseling, one of the outreach media used is Montage Art. The research aims to determine the level of knowledge about brushing teeth before and after being given counseling using montage art media. The type of research used in this research is descriptive with a survey method which aims to determine the description of the level of knowledge about brushing teeth before and after being given counseling using montage art media to students of Class III Sdn 067247 Kec. Field of Benefits. The total research sample was 30 people. The results of the research obtained the level of knowledge about brushing teeth before being given counseling using montage art media, namely good criteria for 16 people (53.3%), medium criteria for 12 people (40%), and bad criteria for 2 people (6.7%) . Meanwhile, the level of knowledge after being given counseling using montage art media was good criteria for 25 people (83.3%), medium criteria for 5 people (16.7%), and there were no bad criteria. Counseling using montage art media can change the knowledge of Class III students at SDN 067247 Kec. Medan Tuntungan by carrying out LGTC (Look, Cut, Stick, and Tell Again) activities about tooth brushing knowledge. It is hoped that students will apply good and correct methods of brushing their teeth in life according to the recommendations of researchers.